Pengaruh Arang Tempurung Kelapa Terhadap Kuat Tekan Beton Dengan Perendaman Air Laut, Air Tawar, Air Sungai Dan Air Kapur - Syafrin Muwardin, Dimas Langga C. Galuh, Iskandar Yasin (Department of Civil Engineering, Faculty of Engineer, Universitas Sarjanawiyata Tamansiswa, 2019)
Construction in the field of construction is currently progressing very rapidly. This can not be separated from the demands of the community's needs for highly developed infrastructure, such as bridges with long spans, high-rise buildings and other facilities. This also causes the use of natural resource materials to increase rapidly, while the available resources are limited in number. To overcome this problem it is necessary to find alternatives that are easy to obtain and do not cause environmental problems.In this study using coconut shell charcoal as an ingredient of added sand with the percentage of coconut shell charcoal mixture 5% in the variation of immersion using sea water, fresh water, river water and limestone water which aims to determine how much the maximum compressive strength of each variation of immersion water. The concrete press test was carried out at 28 days of concrete.The results of the maximum compressive strength of each variation of immersion water are soaking river water of 24.06 N / mm², immersion of well water by 21.15 N / mm², immersion of lime water is 21.29 N / mm² and soaking of seawater is 23, 27 N / mm².